ANALISIS PENGGUNAAN METODE RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNING, AND CAPITAL (RGEC) DALAM MENGUKUR KESEHATAN BANK PADA BANK UMUM SYARIAH DI INDONESIA PERIODE 2012-2014 - Khalil, Muhammad; Fuadi, Raida (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
This research aims to analyze the usage of Risk Profile, Good Corporate Governance, Earning and Capital (RGEC) method to measure bank health on Islamic Banks in Indonesia between 2012-2014. This research used RGEC method which is an innovation from Capital, Asset, Management, Earning, Liquidity and Sensitivity to Market Risk (CAMELS) method to analyze and measure bank health by using composite rank calculation on financial report. Total Islamic banks in this research are 11 banks, which are Bank Syariah Mandiri, BNI Syariah, Bank Muamalat Syariah, Bank Mega Syariah, BRI Syariah, BCA Syariah, Bank Syariah Bukopin, Bank BJB Syariah, Bank Panin Syariah, Bank Maybank Syariah and Bank Victoria Syariah. The result during 2012-2014 period showed that bank with the healthiest predicate in 2012 was Bank Muamalat Syariah, and in 2013 were Bank BNI Syariah and Bank Mega Syariah 2013 also in 2014 were bank Bank Panin Syariah and Bank BNI Syariah.Keywords: RGEC Method, Risk Base Bank Rating